THE CREATION OF CHINGIZ AITMATOV AND THE REFLECTION OF NATIONALITY IN THE STORY "JAMILA" - M. Jamoliddinov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Genghis Aitmatov, a great writer and public figure of Kyrgyz literature, is a writer who made a great contribution to the development of world literature.